Influence of MWCNTs Doping on the Structure and Properties of PEDOT:PSS Films. (22nd November 2009) - Li, Jiao; Liu, Juncheng; Gao, Congjie; Zhang, Jinling; Sun, Hanbin
Abstract : Poly(3, 4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) doped with multi-walled carbon nanotubes (MWCNTs) films is fabricated on quartz substrates by spin coating method. The effects of MWCNTs on the structure and properties of PEDOT:PSS film have been investigated. X-ray diffractometer (XRD) and Fourier transform Raman spectroscopy (FTRM) show that the crystallization behavior and the main chain of PEDOT:PSS are not changed. Atomic force microscopy (AFM) shows that individual nanotubes are well dispersed in the PEDOT:PSS matrix. Moreover, some nanotubes overlap into a net-like structure, forming new conductive channels, which can enhance efficiently the film conductivity. The conductivity of PEDOT:PSS film doped with a lower percentage of MWCNTs (0.2 wt%) is 9.16 S/cm, higher than that of pure PEDOT:PSS film (0.28 S/cm), although the optical transmission of PEDOT:PSS decreases a little after the addition of MWCNTs. The interaction between MWCNTs and PEDOT:PSS during melt mixing is also given a possible explanation.